Evaluasi Penerapan E-Government Di Pemerintah Kabupaten Sumbawa Besar Menggunakan Kerangka Kerja Sistem Pemerintahan Berbasis Elektronik (SPBE) - Hemy Dwi Pratiwi; Widhy Hayuhardhika Nugraha Putra; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The Sumbawa Regency Government, as part of the Indonesian government agency, has begun to carry out improvements to the performance of its government in line with the government's bureaucratic reform program, which is to reorganize, change, improve and perfect the bureaucracy to become more efficient, effective and productive. However, on the results of the Government Institution Performance Accountability Assessment System (SAKIP), for 2 years (2017-2018), Sumbawa Regency won the "CC" title in West Nusa Tenggara Province. E-government concept is to create friendly, convenient, transparent and inexpensive interactions between government and community institutions (Government to Citizen), government agencies and business government (Government to Business Enterprises) and relationships between government agencies (Inter Agency Relationship). Therefore the use of e-government application is also expected to improve the productivity and efficiency of the bureaucracy and increase economic growth. This study aims to assess the application of e-government using the SPBE framework on the SPBE service dimension in Sumbawa Regency. The research methodology used is descriptive qualitative data collection using interviews, and observation. Based on the results of the analysis, the application of e-government in the SPBE service dimension in Sumbawa Regency is in the category of "good" with an average value of 2.80 on each indicator. From the results of the study, recommendations for improving the implementation of e-government are then based on each indicator in the SPBE service to achieve the "satisfactory" rating based on the SPBE framework.